"Push-Through" Rod Passage Technique for the Improvement of Lumbar Lordosis and Sagittal Balance in Minimally Invasive Adult Degenerative Scoliosis Surgery. Issue 8 (October 2016) - Haque, Raqeeb M.; Uddin, Omar M.; Ahmed, Yousef; El Ahmadieh, Tarek Y.; Hashmi, Sohaib Z.; Shah, Amir; Fessler, Richard G.
Abstract : Summary of Background Data: Traditional open surgical techniques for correction of adult degenerative scoliosis (ADS) are often associated with increased blood loss, postoperative pain, and complications. Minimally invasive (MIS) techniques have been utilized to address these issues; however, concerns regarding improving certain alignment parameters have been raised. Objective: A new "push-through" technique for MIS correction of ADS has been developed wherein a rod is bent before its placement into the screw heads and then contoured further to yield improved correction of radiographic parameters. Methods and Study Design: Preoperative and postoperative radiographic measurements of 3 patients who underwent MIS correction of scoliosis using the "push-through" technique were compared with 22 prior patients who had received traditional MIS correction. All patients received staged correction of scoliosis. The first stage involved insertion of lateral lumbar interbodies. Standing x-rays were then evaluated for overall global balance. The second stage involved appropriate MIS facetectomies, facet fusions, posterior transforaminal interbodies at lower lumbar segments, and finally the placement of rods. Technique Overview: (1) A long rod composed of titanium is bent with a mild lordosis and passed through the extensions of the screw heads cephalad to caudad. (2) The rod is passed fully through the incision so it extrudes from the caudal end of the construct. At this point, further lordosis is bent into the rods. (3) The rod is then pulled back into the appropriate position. (4) The unnecessary cephalad rod is then cut to appropriate length with a circular saw. (5) Rod reducers are then sequentially lowered and tightened to achieve the desired correction. Results: Mean age for all patients was 66.02 years. Preoperative coronal Cobb, sagittal vertical axis (SVA), and pelvic incidence (PI) were similar in all patients, whereas lumbar lordosis (LL) was smaller (15.27 vs. 29.85 degrees, P =0.00389) and pelvic tilt (PT) was larger (37.00 vs. 27.00 degrees, P =0.00011) in "push-through" patients. Postoperatively, "pushthrough" patients experienced greater correction of LL (21.93 vs. 3.70 degrees, P =0.00001), PI-LL (−18.57 vs. −0.26 degrees, P =0.00471), PT (−7.67 vs. −0.40 degrees, P =0.00341), SVA (−40.67 mm vs. 0.95 mm, P =0.05846), and coronal Cobb (−20.23 vs. −18.76 degrees, P =0.75). Conclusions: This new method of contouring a rod enables improved LL. This technique is easy to perform and can be a valuable tool in treating ADS using MIS techniques.